Midwives' Role in Managing Pregnant Women with Mental Health Issues and Disorders in Developing Countries: A Rapid Review - Rohani, Rohani; Pratiwi, Cesa Septiana (Poltekita : Jurnal Ilmu Kesehatan, 2024)
The mental health issues of pregnant women must be detected early and addressed quickly to prevent negative impacts on the mother, fetus, and newborn. This review aims to identify current evidence on the role of midwives in managing pregnant women with mental health problems and disorders in developing countries. The review method employed is a rapid review, utilizing the PRISMA-ScR checklist, the PCC framework, and a critical appraisal tool adapted from the Joanna Briggs Institute (JBI) for assessment. A literature search was conducted across three databases (PubMed, Wiley, Science Direct), Google Scholar, and Research Rabbit, with inclusion criteria consisting of all original articles in English or Indonesian from 2018 to 2023, discussing management, midwives' roles, inhibiting factors, supporting factors, and full-text availability. From the search, 300 articles were retrieved, of which 7 were duplicates. Screening based on inclusion criteria yielded 7 articles published in 2020 (2 articles), and 2021 (2 articles),. and 2023 (3 articles), with qualitative design (n=4, 57.2%) and cross-sectional design (n=3, 42.8%). Two articles were from Ghana, while the remaining five were from Uganda, Sri Lanka, Ethiopia, China, and India. Three themes emerged regarding the midwives' role in managing pregnant women with mental health problems and disorders: screening, referral, barriers, and supportive factors. Further research is needed to test the effectiveness of midwives' screening for maternal mental health and to develop and evaluate integrated perinatal mental health service models.